The Fiddle Burning Priest of Mabou - McDavid, Jodi (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2008)
Father Kenneth MacDonald was the priest of Mabou, Cape Breton, from 1865-1894. Written accounts detail him as a strict disciplinarian and social advocate: against the consumption of alcohol; disliking picnics; and telling parishioners how to vote. But the written word seems to leave out the one event that locals still discuss: how he went door to door and burnt their fiddles. Although a small rural town, Mabou is one of cultural importance in Cape Breton, considered the heart of Cape Breton traditional music. Of central iconic importance in both the folk and popular manifestations of this music is the fiddle.